The effects of electronic smoking on dental caries and proinflammatory markers: a systematic review and meta-analysis - Tabnjh, Abedelmalek Kalefh; Alizadehgharib, Sara; Campus, Guglielmo; Lingström, Peter (Frontiers in Oral Health, 2025)
IntroductionSmoking and the use of electronic cigarettes (e-cigs) are common practices that have significant consequences for oral health. Although the negative impact of traditional tobacco products on oral tissues is widely known, the emergence of e-cigs poses a new obstacle. This review summarises existing data on the influence of e-cigs on oral health, with a specific emphasis on dental caries and pro-inflammatory agents.MethodsA comprehensive search was conducted via PubMed, Web of Science, Embase, and Scopus to identify relevant studies published until September 2024. The structured search strategy uncovered 42 articles that were read in full text. The included articles consisted of clinical trials, observational studies, and laboratory investigations that examined the impact of e-cig aerosol on oral bacteria and pro-inflammatory markers and its potential to contribute to dental caries.ResultsThe findings indicate that e-cig users may have a higher prevalence of dental caries compared with non-smokers. Most studies focusing on bacteria showed that vaping may inhibit normal flora, giving cariogenic bacteria a chance to grow more. This finding indicates a notable oral health risk associated with vaping. Meta-analyses suggest no effect of using e-cigs on the levels of TNF-α, IL-1β, IL-6, and IL-8 in saliva, even if it may affect their levels in GCF. However, in GCF, only one study reported TNF-α and IL-1β, and only two studies reported IL-6 and IL-8. Nevertheless, the effects of e-cigs on dental caries require further investigation since the data do not provide a clear picture.DiscussionThis review emphasises the necessity for ongoing research to clarify the mechanisms that cause these consequences and to guide public health policies aimed at reducing the harm caused by e-cigarettes.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024537910, PROSPERO (CRD42024537910).